STRENGTHENING ACADEMIC BUSINESS GOVERMENT (ABG) COOPERATION IN EMPOWERING WOMEN THROUGH CORPORATE SOCIAL RESPONSIBILITY (CSR) - Riany Laila Nurwulan; Ine Mariane (Universitas Pasundan, 2018)
This study aims to analyze the implementation of Corporate Social Responsibility CSR) in the perspective of academic, business, and government (government) cooperation by PT. Telkom, Indonesia Tbk in District Kiaracondong Bandung. The research used qualitative descriptive method. The informants were chosen purposively which included representatives of companies, recipient communities, and local government apparatus. Data collection techniques were conducted through a series of in-depth interviews, field observations and documentary studies. The study found that CSR implementation through the empowerment of women in the process involves elements of academia and local government, so that the implementation shows the success and impact on the benefits felt by the community as reflected in the empowerment index. Based on the results of the study recommended that the company establish cooperation also with the district level government.